Analyzing the influence of the Board of Directors, Audit Committee, and Social Responsibility Disclosure on the company's value: Study of Mining Sector Companies Listed on BEI 2021-2023 - Simangunsong, Bangkit Hamonangan; Wiralestari, Wiralestari; Olimsar, Fredy (International Journal of Multidisciplinary Approach Research and Science, 2024)
This research aims to determine the influence of the board of directors, audit committee, and social responsibility disclosure on company value in mining sector companies listed on the Indonesian Stock Exchange in 2021-2023. This type of research is quantitative research. Samples were taken using Purposive Sampling. The sample consisted of 14 companies consisting of 56 mining sector companies listed on the Indonesia Stock Exchange in 2021-2023, so the research data analyzed was 42. The analysis technique used was descriptive statistics and multiple linear regression analysis. The software used to process the data is SPSS version 29 for Windows. The board of directors is measured by looking at the number of directors in a company in the annual report, the audit committee is measured by looking at the number of audits in a company in the annual report and social responsibility disclosure is measured by looking at the disclosure index reported in the company's continuation report. The results of this research partially show that the board of directors influences company value. Meanwhile, the audit committee and disclosure of social responsibility have no effect on the company value of mining companies listed on the Indonesia Stock Exchange.